A Mamoa do Barreiro-um tumulus do Leste de Trás-os-Montes - Sanches, Maria de Jesus; Lebre, Anabela Gomes; Santos, António Manuel (Trabalhos de Antropologia e Etnologia, 2020)
We are revealing herewith the results of an excavation eftécted, under emergency conditions, at the «Barreiro» Barrow. This is a monument with a tumulus located on the eastern part of Trás-os-Montes (council of Mogadouro). The tumulus, in spite of the great destruction caused by the opening of a passageway, by the groundwork for the support of the railway line of «Sabor» and by the subsequent function of the railway, still preserved in the interior, a funerary structure alm.ost intact. This monument is formed by a ditch with a sub-circular outline of about 3 metres in diameter and which was dug on the primitive bedrock. The walls of the ditch were surrounded by small, medium and large schist slabs. The «megalithic» larger slabs were ali found at the East outline of this ditch. The filling of the ditch was intact and there were various votive artfacts on its base, i.e.: a geometric microlith, an arrowhead, a large blade (all these made out of silex), an adze and a biconical jet-black bead, perfurated on the centre. We believe that this under-tumulus burial- presumably done individuallywould date from the first half of the III mil. b.C. However, we are awaiting a more accurate dating through a sample already being analysed by the C14 method.